Spiritual Marketing in Increasing Sales Turnover of Micro, Small, and Medium Enterprises in Indonesia - Agus Wahyu Triatmo; Arif Nugroho; Supandi Supandi; Ade Yuliar (Global Review of Islamic Economics and Business, 2022)
The increasing diversity of modern humans has implications for changes in consumer behavior. Previously, consumers solely relied on logical considerations when selecting products or services, but now this framework has been shifted to encompass broader considerations. This trend forces a shift in the marketing paradigm; from rational marketing to emotional marketing, even continuing to spiritual marketing. This article seeks to examine the implementation of spiritual marketing to increase the sales turnover of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, with a case study of “Komunitas Bubur Sedekah” in Setabelan Banjarsari, Surakarta. This case study applied Hermawan Kertajaya's spiritual marketing theory as a theoretical framework. Data were obtained through in-depth interviews, observation, and documentation. In-depth interviews were held with advisors, porridge sellers, almsgivers, and customers. Observations were conducted to capture data from the porridge business activities. Meanwhile, documentation was utilized to collect data from various social media platforms belonging to the community. The findings of the study indicate that “Bubur Sedekah” is a manifestation of spiritual marketing because it is grounded in ethical spiritual principles, such as theistic, humanistic, and contextual values that bring satisfaction to customers, thus resulting in regular donations. Consequently, the sales turnover of “Bubur Sedekah” has considerably increased, and the sustainability of their business is now assured.